POLA KOMUNIKASI ANTARA ANAK DAN ORANG TUA YANG BERHUBUNGAN JARAK JAUH DALAM MENGATASI KONFLIK (Studi Fenomenologi pada Mahasiswa UPN Veteran Jakarta) - Olga Amelvi Tanjung, (2023)
The development of the times also raises awareness of the importance of education. Educational facilities that are not evenly distributed in each region cause many students from various regions to go out of town to continue their education, especially when they want to pursue higher education. This causes many children and parents to undergo long-distance relationships because of the interests of children's education and causes changes in communication patterns that occur between children and parents, changing communication patterns cause conflicts or obstacles in communication that occur. This study uses a qualitative research method with a constructivism paradigm, and through a phenomenological approach. Data collection was carried out through interviews, literature studies, and documentation. The results of the study show that the communication patterns that occur and the obstacles that occur are caused by various different factors in each family due to different backgrounds, and conflicts are resolved by mutual understanding and communication.